EMC for product designers - Williams, Tim, 1954- (Oxford : Newnes, 2007)
Widely regarded as the standard text on EMC, Tim Williams book provides all the key information needed to meet the requirements of the latest EMC Directive. Most importantly, it shows how to incorporate EMC principles into the product design process, avoiding cost and performance penalties, meeting the needs of specific standards and resulting in a better overall product. As well as covering the very latest legal requirements, the fourth edition has been thoroughly updated in line with the latest best practice in EMC compliance and product design. Coverage has been considerably expanded to include the R & TTE and Automotive EMC Directives, as well the military aerospace standards of DEF STAN 59-41 and DO160E. A new chapter on systems EMC is included, while short case studies demonstrate how EMC product design is put into practice. Tim Williams has worked for a variety of companies as an electronic design engineer over the last 25 years. He has monitored the progress of the EMC Directive and its associated standards since it was first made public. He now runs his own consultancy specialising in EMC design and test advice and training. * Includes the compliance procedures of the latest EMC Directive: 2004/108/EC * Short case studies demonstrating how EMC product design is put into practice. * Packed full with many new chapters including: - The R & TTE Directive and the Automotive EMC Directive looking at compliance aspects of radio and telecom terminal equipment and automotive electronic products - New chapter on military aerospace standards of DEP STAN 59-41 and DO1 60E - New chapter on systems EMC.
Preface; Part 1: Legislation & Standards; Chapter 1: Introduction; Chapter 2: The EMC Directive; Chapter 3: The R & TTE Directive; Chapter 4: Commercial Standards; Chapter 5: Other Standards; Part 2: Testing; Chapter 6: RF Emissions Measurements; Chapter 7: Immunity Tests; Chapter 8: Low requency Tests; Chapter 9: Test Planning; Part 3: Design; Chapter 10: Interference Coupling Mechanisms; Chapter 11: Layout and Grounding; Chapter 12: Digital and Analogue Circuit Design; Chapter 13: Interfaces and Filtering; Chapter 14: Shielding; Chapter 15: Systems EMC; Chapter 16: EMC Management; Appendix A: Design checklist; Appendix B: CAD for EMC; Appendix C: Case studies; Appendix D: Useful tables and formulae; Appendix E: The EU and EEA countries; Glossary; Bibliography; Index.
Previous ed.: 2001.
Includes bibliographical references and index.
Keywords: Electromagnetic compatibility; Electronic books